2013
DOI: 10.4103/0253-7613.106439
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium phosphide-induced genetic and oxidative damages in vitro: Attenuation by Laurus nobilis L. leaf extract

Abstract: Objective:The present investigation was undertaken to assess the protective effect of Laurus nobilis leaf extract (LNE) against aluminum phosphide (AIP)-induced genotoxic and oxidative damages stress in cultured human blood cells in the presence of a metabolic activator (S9 mix).Materials and Methods:Sister chromatid exchange (SCE) and chromosome aberration (CA) assays were used to assess AlP-induced genotoxicity and to establish the protective effects of LNE. In addition, we determined total antioxidant capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The defensive effects of the leaf extract of Laurus nobilis L. (LNE), a plant with antioxidant and antibacterial properties, against AlP-induced genotoxicity and oxidative damages were investigated in cultured human blood cells [ 56 ]. Co-application of LNE (25, 50, 100 and 200 mg/l) and AlP (58 mg/l) decreased the total oxidative levels but increased the total antioxidant capacity (TAC) as compared to the controls.…”
Section: Laurus Nobilis Lmentioning
confidence: 99%
“…The defensive effects of the leaf extract of Laurus nobilis L. (LNE), a plant with antioxidant and antibacterial properties, against AlP-induced genotoxicity and oxidative damages were investigated in cultured human blood cells [ 56 ]. Co-application of LNE (25, 50, 100 and 200 mg/l) and AlP (58 mg/l) decreased the total oxidative levels but increased the total antioxidant capacity (TAC) as compared to the controls.…”
Section: Laurus Nobilis Lmentioning
confidence: 99%
“…(b) AlP also increased the frequency of MN and altered the levels of TAC and TOS, and (c) this damage was significantly reduced by combining both compounds, since LNE reduced the oxidative stress and suppressed the genetic damage induced by AlP in bone marrow cells in vivo. In conclusion, the results suggested that the protective effect of LNE could be attributed to the laurel’s ability to eliminate free radicals [122,123].…”
Section: Antigenotoxic Plants and Vegetablesmentioning
confidence: 99%
“…Drugs of herbal origin have been used in traditional systems of medicine since ancient times, and many researchers have benefited from medicinal plants to prevent oxidative stress. [ 13 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%